INKULTURASI TATA PERAYAAN PERKAWINAN GEREJA KATOLIK TERHADAP KULTUR BATAK TOBA DALAM PENGGUNAAN BORAS SI PIR NI TONDI - Ricky Fernando Sitio (Jurnal Pelayanan Pastoral, 2023)
Every tribe definitely has customs or traditions that are still practiced today. These customs or traditions can include birth, marriage, and even death. One tribe that has many traditions is the Toba Batak tribe, especially in marriage rites. Marriage in Toba Batak culture has very noble values. In the Catholic Church's liturgy, marriage rites also have sacred valuesA meeting of marriage procedures in the Catholic Church and one of the elements of Toba Batak culture is needed to maintain the faith of the faithful. The liturgy is one of the means of mission in the midst of the faithful. Amidst the cultural diversity that exists in Indonesia, the Catholic Church is also responsible for maintaining local culture. The Catholic Church's marriage procedures open opportunities for elements of local culture to be expressed in the liturgy. Boras si pir ni tondi is one of the elements of Toba Batak culture which is suitable to be included in the inculturation of Catholic marriage procedures. By incorporating boras si pir ni tondi as a form of expression from local culture into the liturgy, the Church has high hopes that local culture will be preserved, the people's faith is always maintained, and the people can have a longing to always meet God. The presence of the Church has always been a link between local customs and faith in God.